A new MBC-TSI topology for microinverter PV application - Razi, Atikah; Hidayat, M. Nabil; Jidin, Auzani; Shukor, Syahar Azali Ab; Noor, S.Z.M. (2023)
This paper presents the design of simulation model of the proposed Multilevel Boost Converter (MBC)-Three Switch Inverter (TSI) for Self-Consumption (SELCO) or known as microinverter in Off-grid Photovoltaic (OGPV) system. Individual PV without array combination is the applied rule towards Microinverter PV panel. The proposed MBC-TSI topology utilize only two isolated individual PV panel for a new approach toward two-stage microinverter (TSM) PV configuration. Conventional H-bridge topology with a total of 7 identical unit of PV panels and H-Bridge topology is taken for reference study aims for 230Vrms PV system with voltage gain almost the same with the proposed topology. The simulation model has been developed using MATLAB Simulink at Standard Test Condition (STC) with open loop switching technique adopted by implementing the switching signals produced by the pulse generator block. The steady-state simulation results show that the proposed MBC-TSI topology successfully generated a voltage gain, AV of 7.34 through reduced number of PV panel (2-unit PV instead of 7-unit PV from the reference study) and generated a balanced 3-level 230Vrms output with voltage and current harmonic percentage of 48.34% and 16.47% respectively. Thus, proved the proposed topology offering a new approach towards TSM in SELCO PV network.